The Paradox Between Universalism of Human Rights and Relativism of Culture - Amit Kumar Singh (Jember University Press, 2020)
The rising tide of Honour killings against Hindu women and their justified murder in the name of culture by their parents/relatives, superficially reflects the tension between traditional and modern values in India. At a deeper level, cases of Honour killings represent the ongoing struggle between the universality of human rights and cultural relativism. Against this background, this article critically examines the role of universal human rights in relation to cultural relativism whilst assessing the values that claim to support honour killings in Indian culture. This article will examine the universalism of human rights and their influence on gender-based violence- especially relating to honour killings in North India. In addition, I will argue for an approach (drawing on the seminal work of Donnelly who proposed ‘relative universalism of human rights’) allowing the tension between universality and particularity/relativism can be reconciled.